Risk of non‐tumoural portal vein thrombosis in patients with HCV‐induced cirrhosis after sustained virological response. (23rd July 2021) - Mandorfer, Mattias; Turon, Fanny; Lens, Sabela; Baiges, Anna; García‐Criado, Ángeles; Darnell, Anna; Belmonte, Ernest; Ferrusquía‐Acosta, José; Magaz, Marta; Perez‐Campuzano, Valeria; Olivas, Pol; Bauer, David; et al.
Abstract: Background & Aims: Sustained virological response (SVR) to direct‐acting antivirals ameliorates portal hypertension, improves hepatic function and may reverse the procoagulant state observed in patients with cirrhosis. However, an unexpected incidence of portal vein thrombosis (PVT) immediately after antiviral therapy has recently been reported. Therefore, we analysed the long‐term impact of SVR on the development of non‐tumoural PVT. Methods: Our study comprised of two well‐characterized prospective cohorts (hepatitis C virus '(HCV)‐Cured': n = 354/'HCV‐Active': n = 179) of patients with HCV cirrhosis who underwent standardized ultrasound surveillance. In the main analysis, the event of interest was de novo non‐tumoural PVT and events known to modify its natural history (orthotopic liver transplantation, transjugular intrahepatic portosystemic shunt, death, tumoural PVT and anticoagulation) were considered as competing risk. Adjusted models were built using propensity scores for baseline covariates. Moreover, predictive factors were investigated by conventional multivariate analysis. Results: Ten (2.8%) patients in the 'HCV‐Cured' cohort developed a non‐tumoural PVT during a median follow‐up of 37.1 months, while 8 (4.5%) patients in the 'HCV‐Active' cohort were diagnosed with non‐tumoural PVT during a median follow‐up of 42.2 months. High Child‐Pugh score was the only independent risk factor for non‐tumoural PVT development and stage A patients were at low risk. Importantly, HCV cure did not decrease the risk of non‐tumoural PVT in inverse probability of treatment‐weighted (IPTW) analysis (subdistribution hazard ratio: 1.31 (95% confidence interval [95% CI]: 0.43‐3.97); P  = .635). In contrast, SVR was associated with a substantial reduction in mortality (IPTW‐adjusted sHR: 0.453 [95% CI: 0.287‐0.715]; P  < .001). Conclusions: The risk of non‐tumoural PVT persists after HCV cure in patients with cirrhosis, despite improving survival. Even after aetiological cure, severity of liver disease remains the main determinant of non‐tumoural PVT development.